2015
DOI: 10.1111/jvp.12275
|View full text |Cite
|
Sign up to set email alerts
|

Comparative plasma pharmacokinetics of ceftiofur sodium and ceftiofur crystalline‐free acid in neonatal calves

Abstract: The objective of this study was to compare the plasma pharmacokinetic profile of ceftiofur crystalline-free acid (CCFA) and ceftiofur sodium in neonatal calves between 4 and 6 days of age. In one group (n = 7), a single dose of CCFA was administered subcutaneously (SQ) at the base of the ear at a dose of 6.6 mg/kg of body weight. In a second group (n = 7), a single dose of ceftiofur sodium was administered SQ in the neck at a dose of 2.2 mg/kg of body weight. Concentrations of desfuroylceftiofur acetamide (DCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
3
7
0
Order By: Relevance
“…In vivo , ceftiofur is rapidly metabolized to DFC, which is the microbiologically active metabolite of CS [ 20 , 39 ]. In several other studies [ 3 , 10 , 18 , 51 ] the dose values of ceftiofur used to calculate pharmacokinetic parameters did not use the total amount of DFC. In this method, conversion of ceftiofur to DFC is followed by derivatization to stabilize DFC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo , ceftiofur is rapidly metabolized to DFC, which is the microbiologically active metabolite of CS [ 20 , 39 ]. In several other studies [ 3 , 10 , 18 , 51 ] the dose values of ceftiofur used to calculate pharmacokinetic parameters did not use the total amount of DFC. In this method, conversion of ceftiofur to DFC is followed by derivatization to stabilize DFC.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial isolates having an MIC value ≤2.0 µ g/m l are considered sensitive to CS according to current CLSI guidelines (National Committee for Clinical Laboratory Standards, 1999). Based on previous studies, a dose regimen of 6.6 mg/kg of CS administered subcutaneously is effective for treatment of severe septic disease in neonatal calves and foals according to the MIC ≤2.0 µ g/m l for >90% of the 12-hr study duration [ 18 , 51 ]. Therefore, the choice of 2.0 µ g/m l as the most effective concentration of CS for endotoxemic shock resulting from E. coli appears to be suitable according to current data and CLSI.…”
Section: Discussionmentioning
confidence: 99%
“…Similar half-lives (p = .406) were calculated in cats following a single intravenous and subcutaneous injection (11.29 and 10.69 hr, respectively). Longer half-live (18.1 hr) was reported for ceftiofur sodium in neonatal calves (Woodrow et al, 2016); however, shorter ones were reported in pregnant pony mares (ranging from 2.91 to 4.1 hr; Macpherson et al, 2017) and sheep (in the range of 4.87-7.75 hr; Craigmill et al, 1997). These inconsistencies may be due to the differences in eating habits and/or physiological status.…”
Section: Fernandezmentioning
confidence: 96%
“…The pharmacokinetics profiles of ceftiofur have been determined in horses (Collard et al, 2011;Edwards, Khalfan, Jacobson, Pirie, & Raidal, 2017;Macpherson et al, 2017;Meyer et al, 2009), cattle (Foster, Jacob, Warren, & Papich, 2016;Gorden et al, 2018;Jaglan et al, 1990;Kang et al, 2018;Okker et al, 2002;Wang et al, 2018;Woodrow, Caldwell, Cox, Hines, & Credille, 2016), water buffalo (Nie et al, 2016), camels (Goudah, 2007), goats (Courtin, Craigmill, Wetzlich, Gustafson, & Arndt, 1997;Fernandez-Varon, Carceles-Garcia, Serrano-Rodriguez, & Carceles-Rodriguez, 2016;Waraich, Sidhu, Daundkar, Kaur, & Sharma, 2017), sheep (Craigmill, Brown, Wetzlich, Gustafson, & Arndt, 1997;Nagel, Beltran, Molina, & Althaus, 2012;Rivera-Garcia et al, 2014), elephants (Dumonceaux, Isaza, Koch, & Hunter, 2005), pigs (Sparks et al, 2017;Xiong et al, 2018), avian species (Tell et al, 1998), and fish (Khalil, Shaheen, & Abdou, 2016). Among different species, ceftiofur shared some similar pharmacokinetics behaviors, such as relatively poor distribution, but quick and complete transformation to its active metabolites, desfuroylceftiofur (DCE), and desfuroylceftiofur conjugates (DCEC).…”
mentioning
confidence: 99%
“…Results of multiple pharmacokinetic studies 10,64,65 indicate that, for any given cephalosporin, the plasma elimination half-life in calves is longer than that for adult cattle, and the plasma elimination half-life varies considerably by age and among cephalosporin formulations. For example, the plasma elimination half-life of ceftiofur sodium for calves ≤ 3 months old is almost 3 times that for calves 6 to 9 months old.…”
Section: Cephalosporinsmentioning
confidence: 99%